Extracellular Vesicles From Hepatocytes Are Therapeutic for Toxin-Mediated Fibrosis and Gene Expression in the Liver - Li, Xinlei; Chen, Ruju; Kemper, Sherri; Brigstock, David R. (Frontiers in Cell and Developmental Biology, 2020)
Extracellular vesicles (EVs) are nano-sized membrane-limited organelles that are liberated from their producer cells, traverse the intercellular space, and may interact with other cells resulting in the uptake of the EV molecular payload by the recipient cells which may become functionally reprogrammed as a result. Previous in vitro studies showed that EVs purified from normal mouse AML12 hepatocytes (“EVNorm”) attenuate the pro-fibrogenic activities of activated hepatic stellate cells (HSC), a principal fibrosis-producing cell type in the liver. In a 10-day CCl4 injury model, liver fibrogenesis assessed by expression of hepatic cellular communication factor 2 (CCN2, also known as connective tissue growth factor) or alpha smooth muscle actin (αSMA) was dose-dependently blocked during concurrent administration of EVNorm. Hepatic inflammation and expression of inflammatory cytokines were also reduced by EVNorm. In a 5-week CCl4 fibrosis model in mice, interstitial collagen deposition and mRNA and/or protein for collagen 1a1, αSMA or CCN2 were suppressed following administration of EVNorm over the last 2 weeks. RNA-seq revealed that EVNorm therapy of mice receiving CCl4 for 5 weeks resulted in significant differences (false discovery rate < 0.05) in expression of 233 CCl4-regulated hepatic genes and these were principally associated with fibrosis, cell cycle, cell division, signal transduction, extracellular matrix, heat shock, cytochromes, drug detoxification, adaptive immunity, and membrane trafficking. Selected gene candidates from these groups were verified by qRT-PCR as targets of EVNorm in CCl4-injured livers. Additionally, EVNorm administration resulted in reduced activation of p53, a predicted upstream regulator of 40% of the genes for which expression was altered by EVNorm following CCl4 liver injury. In vitro, EVs from human HepG2 hepatocytes suppressed fibrogenic gene expression in activated mouse HSC and reversed the reduced viability or proliferation of HepG2 cells or AML12 cells exposed to CCl4. Similarly, EVs produced by primary human hepatocytes (PHH) protected PHH or human LX2 HSC from CCl4 -mediated changes in cell number or gene expression in vitro. These findings show that EVs from human or mouse hepatocytes regulate toxin-associated gene expression leading to therapeutic outcomes including suppression of fibrogenesis, hepatocyte damage, and/or inflammation.